PENGARUH LITERASI DIGITAL DAN KEMUDAHAN TEKNOLOGI TERHADAP KEPUTUSAN PELAKU UMKM MENGGUNAKAN PLATFORM DIGITAL DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Tompo, Ismaila (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effect of digital literacy and technology ease on the decision of micro, small, and medium enterprises (UMKM) to use digital platforms in Rappocini District, Makassar City. The rapid development of digital technology has encouraged UMKM to adopt digital platforms to improve business performance; however, differences in digital literacy and perceptions of technology ease remain important challenges. This research employed a quantitative explanatory approach using primary data collected through a survey of UMKM actors in Rappocini District. The sample consisted of UMKM owners selected using a purposive sampling technique. Data were analyzed using multiple linear regression analysis, supported by classical assumption tests. The results show that digital literacy has a positive and significant effect on UMKM decisions to use digital platforms. Technology ease also has a positive and significant effect on the decision to adopt digital platforms. Simultaneously, digital literacy and technology ease significantly influence UMKM decisions in utilizing digital platforms. These findings indicate that improving digital skills and ensuring user-friendly technology are essential factors in accelerating the digital transformation of UMKM. The results of this study are expected to provide practical insights for policymakers and stakeholders in designing strategies to support UMKM digitalization at the local level.